The Age of Intervention: Addiction, Culture, and Narrative During the War on Drugs - Hardin, Ashleigh M. (2016)
While addiction narratives have been a feature of American culture at least since the early 19th century’s temperance tales, the creation of the Johnson Intervention in the late 1960s and the corresponding advent of the War on Drugs waged by U.S. Presidents have wrought significant changes in the stories told about addiction and recovery. These changes reflect broader changes in conceptions of agency and the relationship of subject to culture in the postmodern era. In the way that it iterates the imperatives of the War on Drugs initiated by Richard Nixon, the rhetoric of successive U.S. Presidents provides a compelling heuristic for analyzing popular and literary texts as reflective of the changing shape of addiction and recovery narratives over the last half century. Johnson, by defining addiction, not intoxication, as a break with reality, argued that confronting addicts with narratives of the potential crises could convince them to seek treatment before they hit bottom. Johnson’s version of “reality therapy” thus presented threatened or simulated crises, rather than real ones. Examining presidential rhetoric and popular culture representations of addiction—in horror movies, “very special episodes,” and reality television—this dissertation identifies features of the postmodern Intervention and recovery narrative in fiction by William Peter Blatty, Stephen King, Jay McInerney, Tama Janowitz, David Foster Wallace, and Jess Walter. I demonstrate how the Intervention is key to understanding the cultural products of the War on Drugs and its continued salience in American culture